KEEFEKTIFAN MANAJEMEN LABORATORIUM KIMIA DI SMA NEGERI 1 TAPAKTUAN ACEH SELATAN - Noviza Rizkia; Taslima Taslima (Lantanida Journal, 2022)
Good facilities, effective and efficient chemical laboratory management must be applied so that chemistry practicum activities can be carried out properly. Previous research has shown that the management of chemical laboratories in several high schools has not been carried out properly, so it is necessary to conduct this study at SMA Negeri 1 Tapaktuan, South Aceh. The purpose of this study was to determine the effectiveness of chemical laboratory management at SMA Negeri 1 Tapaktuan, South Aceh. This research was conducted qualitatively accompanied by descriptive analysis. Subjects in this study; principal, person in charge/head of chemical laboratory, laboratory staff and chemistry teacher. Collecting data by observation, interviews and documentation. Next, the research results are classified into 4 aspects of laboratory management which consist of planning, organizing, implementing and monitoring which are divided into 28 criteria. The results obtained are the management of the chemistry laboratory which is well implemented 75%, less good 10.72% and not good 14.28%. The conclusion of this study is that the chemical laboratory management at SMA Negeri 1 Tapaktuan South Aceh has not been effective because it has not reached 80% of all aspects of chemical laboratory management.